ARCHITECTONICS OF THE THREE-LEVEL MODEL OF ADAPTIVE EFFICIENCY OF THE INSTITUTIONAL ENVIRONMENT: THEORETICAL FOUNDATIONS AND STRUCTURAL LOGIC (INNOVATIVE ECONOMY, 2026)
Pylypenko H.M., Fedorova N.Ye.  ARCHITECTONICS OF THE THREE-LEVEL MODEL OF ADAPTIVE EFFICIENCY OF THE INSTITUTIONAL ENVIRONMENT: THEORETICAL FOUNDATIONS AND STRUCTURAL LOGICPurpose. The aim of the study is to substantiate the architectonics of a three-level model of the adaptive efficiency of the institutional environment, which makes it possible to structurally connect the functions of institutions, the conditions of their implementation, and the results of institutional action under the conditions of post-industrial transformations of society, and to create the preconditions for the further operationalization of this model.Methodology of research. The study is based on institutional and evolutionary theory using a systems approach, structural and functional analysis to identify the functions and subfunctions of the institutional environment. A logical and analytical method is applied to construct the three-level architectonics “functions – criteria – components”. A comparative and analytical approach is used to interpret different types of institutional responses to technological challenges. The method of conceptual modelling is employed to build chains “subfunction – dysfunction – criteria – component”, enabling further operationalization and quantitative measurement of adaptive efficiency.Findings. The three-level architectonics of the model of the adaptive efficiency of the institutional environment is substantiated, comprising: the functional level (coordination, distributional, and stimulating functions and their subfunctions as channels of institutional action); the criteria level (conditions for the implementation of institutional functions and parameters of institutional viability); and the component level (agility, plasticity, stability, anticipation, and foresight as forms of institutional response to technological challenges).An algorithm for constructing subfunctional analytical chains is proposed, in which the component of adaptive efficiency is derived from the configuration of weakened implementation of the corresponding subfunction's criteria. This makes it possible to determine the depth and the type of required institutional adaptation (procedural, transformational, stabilizing, or anticipatory). It is shown that the component of adaptive efficiency serves as a system-forming element of the model, integrating the potential of institutions, the conditions for their realization, and the result of institutional response. The algorithm is illustrated using the example of the institutional environment's coordination function and two of its subfunctions. The model creates a basis for the transition from conceptual analysis to the formalized measurement of the adaptive efficiency of the institutional environment.Originality. An integral architectonics of the adaptive efficiency of the institutional environment, based on the three-level logic “functions – criteria – components,” is developed, which, for the first time, integrates the transformational potential of institutions, the conditions of their viability, and the results of institutional adaptation into a single analytical framework. The approach to identifying the components of adaptive efficiency through the type of institutional response to technological challenges is improved, thereby forming the methodological basis for operationalizing the adaptive efficiency of the institutional environment.Practical value. The obtained results may be used for quantitative assessment of adaptive efficiency of institutional environments across countries, cross-country comparative analysis, identification of institutional dysfunctions in technological transformations, and regression-based analysis of the relationship between adaptive efficiency of the institutional environment and technological development. The proposed model provides a basis for developing institutional policy instruments aimed at enhancing the capacity of the societal system to integrate breakthrough technologies and reducing structural barriers to societal development.Key words: institutional environment, adaptive efficiency of the institutional environment, technological change, institutional functions, institutional subfunctions, criteria of adaptive efficiency of the institutional environment, components of adaptive efficiency of the institutional environment, agility, plasticity, stability, anticipation, foresight.
Keywords: institutional environment; adaptive efficiency of the institutional environment; technological change; institutional functions; institutional subfunctions; criteria of adaptive efficiency of the institutional environment; components of adaptive efficiency of the institutional environment; agility; plasticity; stability; anticipation; foresight